The Six Brandenburg Concertos and the Four Orchestral Suites in Full Score - BACH, Johann Sebastian (Dover Publication, 1976)
Buku ini merupakan partitur lengkap untuk musik orkes. Partitur Branderburg Concertos terdiri dari: - No. 1 in F Major ( violino piccolo, 3 oboes, 2 horns, bassoon, strings and continuo)- No. 2 in F Major (violin, recorder/flute, oboe trumpet, strings and continuo)- No. 3 in G Major (strings and continuo)- No. 4 in G major ( violin, 2 recorders/flutes, strings and continuo- No. 5 in D Major (clavier, violin, flute, strings and continuo)- No. 6 in B-flat Major (strings minus violins, and continuo)Sedangkan bagian Orchestral Suites (Ouverturen)terdiri dari:- No. 1 in C Major (Woodwinds, strings and continuo)- No. 2 in B Minor (flute, strings and continuo)- No. 3 in D Major (oboes, trumpets, timpani, strings and continuo)- No. 4 in D Major (oboe, Bassoon, trumpets, timpani, strings and continuo)